(untitled) (Cambridge, 1987)
These two volumes, with their focus on econometrics, contain papers delivered at the Fifth World Congress held in l985. Designed to make material accessible to a general audience of economists, these papers should be helpful to anyone with training in economics who wishes to follow new ideas and tendencies in the subject. Advances in Econometrics, Fifth World Congress, Volumes 1 & 2 edited by Professor Truman F. Bewley of Yale University, include a wide variety of topics, comprising empirical and policy oriented subjects as well as theoretical and methodological ones.
Keywords: Econometrics,Econometric models,Toán kinh tế,Mô hình toán kinh tế; Congresses,Congresses,Hội nghị,Hội nghị